Artificial Intelligence in Military Technology Sociological, cultural and ethical perspectives - Talves, Kairi; Spreen, Dierk; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This is an open access book. This volume critically examines challenges in the field of current and future military technology from a transdisciplinary lens. It helps objectify the debate around the development of Lethal Autonomous Weapon Systems (LAWS). The volume offers a differentiated, informed and open approach to military artificial intelligence (AI) applications in the public realm, in politics and in the military itself. The contributions weigh the risks that artificially intelligent automation, like any new technology, brings, against technological innovation and progress. They address the issues of testing new technologies, implementing them socially and reflecting on their use, along with questions of unintended consequences of such technologies. The volume is divided into three parts. The first discusses perspectives on AI; how AI systems are understood by the public, by soldiers, and in cultural discourses. The focus is on (but not limited to) military applications. The second part focuses on the challenges and changes posed by the use of AI in military conflicts and addresses issues of how to deal with them. The third part examines the communication challenges posed by the implementation of AI in the military and the associated opportunities and risks. This highly topical and timely volume is for researchers and students across disciplines who have an interest in military technology and those interested in AI and new technology.
Introduction-. Part I The Robot Understanding -- Fear for the Robots Cultural Perspectives about the Fear for Technology -- Humanism or Transhumanism Critique of transhumanism -- Military Robots in Science Fiction -- Overview of the international policy perspective on AI in the military -- What do the soldiers think A small country perspective -- Part 2 AI and Military Conflict Human factor and military technology in warfare a historical perspective -- Control the AIs An engineering perspective -- AI in the Military from the Perspective of the Innere Führung -- Autonomous Weapons Systems A Review of Legal and Ethical Issues -- Overview on the systems theory approach to war and violent conflicts -- The impact of cultural factors on trust technology in the case of strategic decision making -- Challenges of communicating military innovation -- Hybrid Warfare and Defence of Discourse De legitimization of the western political system -- Autonomy and communication the FCAS process -- Cognitive warfare and Bourdieu s theory doxa and illusio marching into cognitive battle -- Exploring and controlling the AI A Human Factors and Human Systems Integration Approach.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Technology -- Sociological aspects; Political sociology; Politics and war; Security, International; Science, Technology and Society; Political Sociology; Military and Defence Studies; International Security Studies